The Concordat of 1953 and the Catholic Spain - Martín de Santa Olalla Saludes, Pablo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The object of the present article is to analyze the development of the Concordat of 1953 in the sense of detecting the main elements of conflict that arose during the application of the same one, particularly from the ending of the Council Vatican Second. The need of the Catholic Church to affirm her independence respect to the temporary power led in Spain to an increasing conflict among the Catholic Church and the State that would finish with the dismantlement of the Concordat and its substitution, already during the Transition to the democracy, for agreements of partial character.